Believing one's own press: the causes and consequences of CEO celebrity - Hayward, Mathew L. A.; Rindova, Violina P.; Pollock, Timothy G. (Strategic Management Journal, 2004)
Abstract This theoretical article introduces the construct of CEO celebrity in order to explain how the tendency of journalists to attribute a firm's actions and outcomes to the volition of its CEO affects such firm. In the model developed here, journalists celebrate a CEO whose firm takes strategic actions that are distinctive and consistent by attributing such actions and performance to the firm's CEO. In so doing, journalists over‐attribute a firm's actions and outcomes to the disposition of its CEO rather than to broader situational factors. A CEO who internalizes such celebrity will also tend to believe this over‐attribution and become overconfident about the efficacy of her past actions and future abilities. Hubris arises when CEO overconfidence results in problematic firm decisions, including undue persistence with actions that produce celebrity. Copyright © 2004 John Wiley & Sons, Ltd.